2018
DOI: 10.3390/molecules23030598
|View full text |Cite
|
Sign up to set email alerts
|

Cis–Trans Configuration of Coumaric Acid Acylation Affects the Spectral and Colorimetric Properties of Anthocyanins

Abstract: The color expression of anthocyanins can be affected by a variety of environmental factors and structural characteristics. Anthocyanin acylation (type and number of acids) is known to be key, but the influence of acyl isomers (with unique stereochemistries) remains to be explored. The objective of this study was to investigate the effects of cis–trans configuration of the acylating group on the spectral and colorimetric properties of anthocyanins. Petunidin-3-rutinoside-5-glucoside (Pt-3-rut-5-glu) and Delphin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 36 publications
(59 reference statements)
1
15
0
1
Order By: Relevance
“…The chromatogram (Fig 1) shows the main jumps: at 10.54 min - delphinidin (Glu), 13.38 min - delphinidin (Rut), 16.64 min - cyanidin (Glu), which indicates that these substances are the main ones in the analyzed extract. Delphinidin and cyanidin are anthocyanidins, they are found in many bright blue-red fruits and berries, such as Manitoba berries, Saskatoon berry (Hosseinian and Beta 2007), eggplant (Sigurdson et al 2018), more delphinidin will be collected. Cyanidin is the most common in raspberries, strawberries (Hosseinian and Beta 2007), and black chokeberry (Jurikova et al 2017), sour cherry (Ertan et al 2018) in apple skin (Ban et al 2009), acai (Yamaguchi et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The chromatogram (Fig 1) shows the main jumps: at 10.54 min - delphinidin (Glu), 13.38 min - delphinidin (Rut), 16.64 min - cyanidin (Glu), which indicates that these substances are the main ones in the analyzed extract. Delphinidin and cyanidin are anthocyanidins, they are found in many bright blue-red fruits and berries, such as Manitoba berries, Saskatoon berry (Hosseinian and Beta 2007), eggplant (Sigurdson et al 2018), more delphinidin will be collected. Cyanidin is the most common in raspberries, strawberries (Hosseinian and Beta 2007), and black chokeberry (Jurikova et al 2017), sour cherry (Ertan et al 2018) in apple skin (Ban et al 2009), acai (Yamaguchi et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…This conforms to the general characteristic of flavylium compounds, where the distinctly absorbing cation converts into colorless hemiketal and cis - and trans -chalcone forms ( Mazza and Brouillard, 1990 ; Pina et al, 2012 ). At higher pH various anionic quinonoidal bases are created ( Mazza and Brouillard, 1990 ; Pina et al, 2012 ; Rakić et al, 2015 ; Dangles and Fenger, 2018 ; Sigurdson et al, 2018 ), which process can be approximated with a two-component logistic function. The differences in the absorbance spectra of Figures 2 , 3 in the long-wavelength range suggest that the absorption spectra of the quinonoidal bases depend on being cyanidin- or pelargonidin-based derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that the petunidin-3-trans-p-coumaroyl-rutinoside-5-glucoside isolate contributed most of the color expression of the black goji extract. It also showed superior stability compared to crude extracts over time [24,25].…”
Section: Introductionmentioning
confidence: 99%